Combining Self-Affirmation and Implementation Intentions: Evidence of Detrimental Effects on Behavioral Outcomes. Issue 2 (24th October 2013) - Jessop, Donna C.; Sparks, Paul; Buckland, Nicola; Harris, Peter R.; Churchill, Sue
Abstract: Background: There is limited evidence that self-affirmation manipulations can promote health behavior change. Purpose: The purpose of this study was to explore whether the efficacy of a self-affirmation manipulation at promoting exercise could be enhanced by an implementation intention intervention. Methods: Participants (Study 1 N = 120, Study 2 N = 116) were allocated to one of four conditions resulting from the two (self-affirmation manipulation: no affirmation, affirmation) by two (implementation intention manipulation: no implementation intention, implementation intention) experimental design. Exercise behavior was assessed 1 week post-intervention. Results: Contrary to prediction, those participants receiving both manipulations were significantly less likely to increase the amount they exercised compared to those receiving only the self-affirmation manipulation. Conclusion: Incorporating an implementation intention manipulation alongside a self-affirmation manipulation had a detrimental effect on exercise behavior; participants receiving both manipulations exercised significantly less in the week following the intervention.